A solar cell and a method of manufacturing the same
Patent Information
- Application Number
- CN202611225566.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
但是,POE胶膜也存在一些缺陷,POE分子链上缺乏极性基团,是一种典型的非极性聚合物,这使得POE封装胶膜对玻璃及背板的粘结性能远不及EVA封装胶膜;此外,POE胶膜还存在收缩率大及耐冲击性差的缺陷
1、本发明制备了一种太阳能电池,对该太阳能电池用的封装材料进行了优化改进处理,制备得到了改性POE材料用作封装材料。相比较于传统的POE材料,本发明制备的改性POE材料具有更好的粘结性、耐冲击性以及抗收缩性,同时还对光具有一定的增透性,从而使得电池的光学效率更高。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, and more specifically to a solar cell and its fabrication method. Background Technology
[0002] A solar cell is a thin photovoltaic semiconductor wafer that directly generates electricity using sunlight. Also known as a "solar chip" or "photovoltaic cell," it can instantly output voltage and generate current when a circuit is established, provided it receives sufficient illumination. A solar cell module includes solar cells, a glass cover, a backsheet material, and an encapsulating film. The encapsulating film supports and secures the solar cells, maintains high solar transmittance, isolates the cells from harmful environmental factors, ensures the module's electrical insulation performance, and guarantees thermal conductivity. It also prevents the encapsulated cells from contacting air and moisture in the atmosphere.
[0003] Currently, the most widely used encapsulation material on the market is ethylene-vinyl acetate polymer (EVA). However, EVA films have been found to have drawbacks such as yellowing over time and insufficient resistance to UV aging. POE plastic is a thermoplastic elastomer produced by in-situ polymerization of ethylene and octene using a metallocene catalyst, abbreviated as ethylene-octene copolymer (POE). The flexible, coiled structure of octene chains and the crystalline ethylene chains act as physical crosslinking points, giving it both excellent toughness and good processability. POE plastic molecules lack unsaturated double bonds, resulting in excellent aging resistance. Compared to EVA films, it has higher water vapor barrier properties, superior weather resistance, and stronger anti-interference performance, making POE films a promising direction for encapsulation material development. However, POE films also have some drawbacks. The lack of polar groups in the POE molecular chain makes it a typical non-polar polymer, resulting in significantly weaker adhesion to glass and backsheets compared to EVA films. Furthermore, POE films also suffer from high shrinkage and poor impact resistance. Therefore, there is a current market demand for a POE film encapsulation material that has good bonding strength, low shrinkage, and impact resistance. Summary of the Invention
[0004] In view of the problems existing in the prior art, the purpose of this invention is to provide a solar cell and a method for its preparation.
[0005] The objective of this invention is achieved through the following technical solution: In a first aspect, the present invention provides a solar cell, comprising, from top to bottom, a cover plate, a first encapsulation layer, a solar panel, a second encapsulation layer, and a backsheet; wherein the first encapsulation layer and the second encapsulation layer are both made of encapsulation material.
[0006] Preferably, the cover plate is made of a light-transmitting material, and an anti-reflective film layer is provided on the upper surface of the cover plate.
[0007] Preferably, the upper surface of the solar panel is provided with a metal electrode, which extends to the outside of the solar panel via a solder strip and is connected to other electrodes.
[0008] Preferably, the encapsulation material is a modified POE material, and the preparation method includes: S1. Mix ytterbium silicide (YbSi2) particles, polyvinyl alcohol and deionized water evenly at room temperature, then add epoxy silane coupling agent, pour into a planetary ball mill under nitrogen protection and ball mill. After ball milling, filter the ball milling material, wash with water at least three times, and vacuum dry to obtain epoxidized nano-ytterbium silicide particles. S2. Mix 2-amino-1,3,5-triazine and anhydrous ethanol, dissolve them completely, add epoxidized ytterbium nanoparticles, heat to reflux reaction, after the reaction is completed, remove the solvent under reduced pressure, wash with water three times, and vacuum dry to obtain the reinforcing modifier. S3. After mixing the POE resin and the solvent tetrahydrofuran evenly, add the reinforcing modifier, stir thoroughly until evenly mixed, remove the solvent under reduced pressure, and the modified POE material is obtained.
[0009] Preferably, in S1, polyvinyl alcohol is one of PVA 1599, PVA 1699, and PVA 1799.
[0010] Preferably, in S1, the particle size of the ytterbium silicide particles is 100±20μm.
[0011] Preferably, in S1, the epoxy silane coupling agent is any one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltriethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane, and γ-(2,3-epoxypropoxy)propylmethyldiethoxysilane.
[0012] Preferably, in S1, the mass-volume ratio of ytterbium silicide particles, polyvinyl alcohol, epoxy silane coupling agent and deionized water is 10g:(0.6-1.2)g:(1-2)g:(5-7)mL.
[0013] Preferably, in step S1, the ball-to-material ratio is 4-8:1, the ball milling speed is 300-500 r / min, and the ball milling time is 3-8 h.
[0014] Preferably, in S2, the mass-volume ratio of epoxidized ytterbium nanoparticles, 2-amino-1,3,5-triazine, and anhydrous ethanol is 1 g : (1.8-3.6) g : (10-20) mL.
[0015] Preferably, in step S2, the reflux reaction temperature is 65-75°C and the reflux reaction time is 4-10 hours.
[0016] Preferably, in step S3, the POE resin is any one of POE 0201, POE 0203, and POE 5101.
[0017] Preferably, in S3, the mass-volume ratio of POE resin, reinforcing modifier, and tetrahydrofuran is 1g:(0.12-0.24)g:(4-8)g.
[0018] Secondly, the present invention provides a method for preparing a solar cell, comprising the following steps: (1) Materials preparation: cover plate, first encapsulation layer, solar panel, second encapsulation layer and back sheet; (2) After cleaning and etching the solar panel, deposit metal electrodes on its surface and connect the solder ribbon to the metal electrodes. (3) The processed solar panels are encapsulated in the following order: cover plate, first encapsulation layer, solar panel, second encapsulation layer and back sheet. After passing the quality inspection, the solar cells are obtained.
[0019] The beneficial effects of this invention are as follows: 1. This invention prepares a solar cell and optimizes and improves the encapsulation material for the solar cell to obtain a modified POE material for use as the encapsulation material. Compared with traditional POE material, the modified POE material prepared in this invention has better adhesion, impact resistance, and shrinkage resistance, while also having a certain degree of light transmittance enhancement, thereby making the cell more optically efficient.
[0020] 2. The modified POE material prepared by this invention is a traditional POE material with the addition of a reinforcing modifier. This reinforcing modifier is prepared by combining epoxidized ytterbium nanoparticles and 2-amino-1,3,5-triazine. The epoxidized ytterbium nanoparticles contain a large number of epoxy groups, which react with the amino groups on the 2-amino-1,3,5-triazine under heating conditions, so that the triazine groups are fixed and coated on the surface of the ytterbium nanoparticles, and finally the reinforcing modifier is obtained.
[0021] 3. In the preparation process of epoxidized ytterbium nanoparticles, a combination of ball milling and surface treatment is adopted. Ytterbium nanoparticles are mixed with epoxy silane coupling agent by ball milling. During the ball milling process, not only are finer nanoparticles obtained, but the surface of the particles is also modified with epoxy groups, thereby obtaining epoxidized ytterbium nanoparticles.
[0022] 4. Testing revealed that the modified POE material prepared by combining the reinforcing modifier of this invention with POE resin not only showed good enhancement in adhesion, impact resistance and shrinkage resistance, but also showed that the light transmittance of the modified POE material was enhanced to a certain extent under the same thickness conditions. This may be due to the unique optical properties of ytterbium silicide and triazine groups. Detailed Implementation
[0023] The technical solution of the present invention is illustrated below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. Furthermore, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or defining the scope of the present invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the present invention.
[0024] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.
[0025] The present invention will be further described below with reference to the following embodiments.
[0026] Example 1 A solar cell includes, from top to bottom, a cover plate, a first encapsulation layer, a solar panel, a second encapsulation layer, and a backsheet; wherein, the first encapsulation layer and the second encapsulation layer are both made of encapsulation material; the cover plate is made of light-transmitting material, and an anti-reflection film layer is disposed on the upper surface of the cover plate; a metal electrode is disposed on the upper surface of the solar panel, and the metal electrode extends to the outside of the solar panel through a solder strip and is connected to other electrodes.
[0027] The method for preparing a solar cell includes the following steps: (1) Materials preparation: cover plate, first encapsulation layer, solar panel, second encapsulation layer and back sheet; (2) After cleaning and etching the solar panel, deposit metal electrodes on its surface and connect the solder ribbon to the metal electrodes. (3) The processed solar panels are encapsulated in the following order: cover plate, first encapsulation layer, solar panel, second encapsulation layer and back sheet. After passing the quality inspection, the solar cells are obtained.
[0028] The encapsulation material is a modified POE material, and the preparation method includes: S1. Ytterbium silicide (YbSi2) particles with a particle size of 100±20μm, polyvinyl alcohol (PVA) 1599, and deionized water were mixed evenly at room temperature. Then, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added. The mass-volume ratio of ytterbium silicide particles, polyvinyl alcohol, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and deionized water was 10g:0.9g:1.5g:6mL. Under nitrogen protection, the mixture was poured into a planetary ball mill and ball-to-material ratio was 6:1. The ball milling speed was 400r / min, and the ball milling time was 5h. After ball milling, the ball milling material was filtered, washed with water at least three times, and vacuum dried to obtain epoxidized nano-ytterbium silicide particles. S2. Mix 2-amino-1,3,5-triazine and anhydrous ethanol, and after fully dissolving, add epoxidized ytterbium nanoparticles. The mass-volume ratio of epoxidized ytterbium nanoparticles, 2-amino-1,3,5-triazine and anhydrous ethanol is 1 g: 2.7 g: 15 mL. Heat to 70 °C and reflux for 7 h. After the reaction is complete, remove the solvent under reduced pressure, wash three times with water, and dry under vacuum to obtain the reinforcing modifier. S3. Apply POE resin POE 5101 (melt flow rate: 2g / 10min, density: 0.902g / cm³). 3 After mixing the POE resin and the solvent tetrahydrofuran evenly, the reinforcing modifier is added. The mass-volume ratio of POE resin, reinforcing modifier and tetrahydrofuran is 1g:0.18g:6g. The mixture is stirred thoroughly until it is evenly mixed. The solvent is removed under reduced pressure to obtain the modified POE material.
[0029] Example 2 One type of solar cell differs from Example 1 in that the preparation method of the encapsulation material is different.
[0030] The encapsulation material is a modified POE material, and the preparation method includes: S1. Ytterbium silicide (YbSi2) particles with a particle size of 100±20μm, polyvinyl alcohol (PVA) 1699, and deionized water were mixed evenly at room temperature. Then, γ-(2,3-epoxypropoxy)propyltriethoxysilane was added. The mass-volume ratio of ytterbium silicide particles, polyvinyl alcohol, γ-(2,3-epoxypropoxy)propyltriethoxysilane, and deionized water was 10g:0.6g:1g:5mL. Under nitrogen protection, the mixture was poured into a planetary ball mill and ball-to-material ratio of 4:1. The ball milling speed was 300r / min, and the ball milling time was 3h. After ball milling, the ball milling material was filtered, washed with water at least three times, and vacuum dried to obtain epoxidized nano-ytterbium silicide particles. S2. Mix 2-amino-1,3,5-triazine and anhydrous ethanol, and after fully dissolving, add epoxidized ytterbium nanoparticles. The mass-volume ratio of epoxidized ytterbium nanoparticles, 2-amino-1,3,5-triazine and anhydrous ethanol is 1 g: 1.8 g: 10 mL. Heat to 65 °C and reflux for 4 h. After the reaction is complete, remove the solvent under reduced pressure, wash three times with water, and dry under vacuum to obtain the reinforcing modifier. S3. After mixing POE resin POE 0201 and solvent tetrahydrofuran evenly, add reinforcing modifier. The mass-volume ratio of POE resin, reinforcing modifier and tetrahydrofuran is 1g:0.12g:4g. Stir thoroughly until evenly mixed, remove solvent under reduced pressure to obtain modified POE material.
[0031] Example 3 One type of solar cell differs from Example 1 in that the preparation method of the encapsulation material is different.
[0032] The encapsulation material is a modified POE material, and the preparation method includes: S1. Ytterbium silicide (YbSi2) particles with a particle size of 100±20μm, polyvinyl alcohol (PVA) 1799, and deionized water were mixed evenly at room temperature. Then, γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane was added. The mass-volume ratio of ytterbium silicide particles, polyvinyl alcohol, γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane, and deionized water was 10g:1.2g:2g:7mL. Under nitrogen protection, the mixture was poured into a planetary ball mill and ball-to-material ratio of 8:1. The ball milling speed was 500r / min, and the ball milling time was 8h. After ball milling, the ball milling material was filtered, washed with water at least three times, and vacuum dried to obtain epoxidized nano-ytterbium silicide particles. S2. Mix 2-amino-1,3,5-triazine and anhydrous ethanol, and after fully dissolving, add epoxidized ytterbium nanoparticles. The mass-volume ratio of epoxidized ytterbium nanoparticles, 2-amino-1,3,5-triazine and anhydrous ethanol is 1 g: 3.6 g: 20 mL. Heat to 75 °C and reflux for 10 h. After the reaction is complete, remove the solvent under reduced pressure, wash three times with water, and dry under vacuum to obtain the reinforcing modifier. S3. After mixing POE resin POE 0203 and solvent tetrahydrofuran evenly, add reinforcing modifier. The mass-volume ratio of POE resin, reinforcing modifier and tetrahydrofuran is 1g:0.24g:8g. Stir thoroughly until evenly mixed, remove solvent under reduced pressure to obtain modified POE material.
[0033] Comparative Example 1 An encapsulation material, which differs from Example 1 in that it is only POE material POE 5101.
[0034] Comparative Example 2 An encapsulation material differs from Example 1 in that the preparation method of the modified POE material is different. The preparation method of the modified POE material includes: S1. Preparation of epoxidized ytterbium silicide nanoparticles, the same as in Example 1; S2. After mixing POE resin POE 5101 and solvent tetrahydrofuran evenly, add epoxidized ytterbium nanoparticles. The mass-volume ratio of POE resin, epoxidized ytterbium nanoparticles and tetrahydrofuran is 1g:0.18g:6g. Stir thoroughly until evenly mixed, remove the solvent under reduced pressure, and the modified POE material is obtained.
[0035] Comparative Example 2 An encapsulation material differs from Example 1 in that the preparation method of the modified POE material is different. The preparation method of the modified POE material includes: After mixing POE resin POE 5101 and solvent tetrahydrofuran evenly, 2-amino-1,3,5-triazine is added. The mass-volume ratio of POE resin, 2-amino-1,3,5-triazine and tetrahydrofuran is 1g:0.18g:6g. The mixture is stirred thoroughly until it is evenly mixed. The solvent is removed under reduced pressure to obtain the modified POE material.
[0036] The encapsulation materials prepared in Example 1 and Comparative Examples 1-3 were compared and tested for performance. Light transmittance was tested according to GB / T 2410-2008, tensile strength was tested according to GB / T 1040.2-2006, impact strength was tested according to GB / T 1843-2008, peel strength was tested according to ASTM D903-98 (with glass substrate), and shrinkage was tested according to ISO 2577.
[0037] The results are shown in Table 1: Table 1. Performance testing of different packaging materials
[0038] As can be seen from Table 1, the encapsulation material prepared in Example 1 of the present invention has higher light transmittance, and also has better tensile strength, peel strength, impact strength and smaller shrinkage.
[0039] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. The illustrative expressions of the above terms in this specification should not be construed as necessarily referring to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0040] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A solar cell, characterized in that, It includes, from top to bottom, a cover plate, a first encapsulation layer, a solar panel, a second encapsulation layer, and a backsheet; wherein, both the first and second encapsulation layers are made of encapsulation material; the encapsulation material is a modified POE material prepared by compounding POE resin and a reinforcing modifier.
2. A solar cell according to claim 1, characterized in that, The cover plate is made of a light-transmitting material, and an anti-reflective film layer is provided on the upper surface of the cover plate.
3. A solar cell according to claim 1, characterized in that, The upper surface of the solar panel is provided with metal electrodes, which extend to the outside of the solar panel via solder strips and are connected to other electrodes.
4. A solar cell according to claim 1, characterized in that, The encapsulation material is a modified POE material, and the preparation method includes: S1. Mix ytterbium silicide (YbSi2) particles, polyvinyl alcohol and deionized water evenly at room temperature, then add epoxy silane coupling agent, pour into a planetary ball mill under nitrogen protection and ball mill. After ball milling, filter the ball milling material, wash with water at least three times, and vacuum dry to obtain epoxidized nano-ytterbium silicide particles. S2. Mix 2-amino-1,3,5-triazine and anhydrous ethanol, dissolve them completely, add epoxidized ytterbium nanoparticles, heat to reflux reaction, after the reaction is completed, remove the solvent under reduced pressure, wash with water three times, and vacuum dry to obtain the reinforcing modifier. S3. After mixing the POE resin and the solvent tetrahydrofuran evenly, add the reinforcing modifier, stir thoroughly until evenly mixed, remove the solvent under reduced pressure, and the modified POE material is obtained.
5. A solar cell according to claim 4, characterized in that, In S1, the epoxy silane coupling agent is any one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltriethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane, and γ-(2,3-epoxypropoxy)propylmethyldiethoxysilane.
6. A solar cell according to claim 4, characterized in that, In S1, the mass-volume ratio of ytterbium silicide particles, polyvinyl alcohol, epoxy silane coupling agent and deionized water is 10g:(0.6-1.2)g:(1-2)g:(5-7)mL.
7. A solar cell according to claim 4, characterized in that, In step S1, the ball-to-material ratio is 4-8:1, the ball milling speed is 300-500 r / min, and the ball milling time is 3-8 h.
8. A solar cell according to claim 4, characterized in that, In S2, the mass-volume ratio of epoxidized ytterbium nanoparticles, 2-amino-1,3,5-triazine, and anhydrous ethanol is 1 g: (1.8-3.6) g: (10-20) mL; in S2, the reflux reaction temperature is 65-75℃, and the reflux reaction time is 4-10 h.
9. A solar cell according to claim 1, characterized in that, In S3, the mass-volume ratio of POE resin, reinforcing modifier and tetrahydrofuran is 1g:(0.12-0.24)g:(4-8)g.
10. A method for preparing a solar cell according to claim 1, characterized in that, Includes the following steps: (1) Prepare the cover plate, first encapsulation layer, solar panel, second encapsulation layer and back sheet for later use; (2) After cleaning and etching the solar panel, deposit metal electrodes on its surface and connect the solder ribbon to the metal electrodes. (3) The processed solar panels are encapsulated in the following order: cover plate, first encapsulation layer, solar panel, second encapsulation layer and back sheet. After passing the quality inspection, the solar cells are obtained.
